Plant yields and fodder quality related characteristics of millet-stylo intercropping systems in the Sahel - Kouamé, C.N.; Powell, J.M.; Renard, C.A.; Quesenberry, K.H. (1993)
The integration of forage legumes into the low-input, cereal-based farming system of the Sahel may be the key to sustaining soil, crop, and livestock production. The objectives of this study were to evaluate the effects of intercropping the forage legumes Stylosanthes fruticosa (Retz.) Slston or S. hamata (L.) R. Br. on grain yield, fodder yield, and crude protein (CP) yield and concentration. Four field trials were conducted on a Psammentic Paleustalf (siliceous, isohyperthermic) soil from 1988 to 1990 at Sadore, Niger. Each Stylosanthes species was grown in alternate single and triple row patterns with millet for 1 and 2 yr, with stylo regrowing from stubble during the second year. Control treatments were sole crops of millet and stylo. Intercropping either Stylosanthes species with millet for 1 yr in alternate single rows did not affect millet grain yield, because of low stylo competition. Total dry matter (DM) harvested of intercrop was similar to that of sole millet, while CP concentration of total DM increased moderately from 43 g kg-1 in sole millet crop to 75 g kg-1 in intercroDuring the second year of association, stylo was very competitive, depressing intercropped millet grain by an average of 67 percent in 1989 and 48 percent in 1990 compared with sole millet grain yield. Total DM and CP yield, and CP concentration of the harvested fodder were, respectively, 1.4, 3.0, and 2.3 times greater in intercrop than sole millet. Millet-stylo intercrops, with each species planted at half its sole crop density, appear to have an advantage in fodder yield and CP over sole millet cropping but not in total grain yield.